2017
DOI: 10.1073/pnas.1619147114
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence that parasites drive eco-evolutionary feedbacks

Abstract: Host resistance to parasites is a rapidly evolving trait that can influence how hosts modify ecosystems. Eco-evolutionary feedbacks may develop if the ecosystem effects of host resistance influence selection on subsequent host generations. In a mesocosm experiment, using a recently diverged (<100 generations) pair of lake and stream three-spined sticklebacks, we tested how experimental exposure to a common fish parasite (Gyrodactylus spp.) affects interactions between hosts and their ecosystems in two environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 54 publications
(59 reference statements)
3
86
0
Order By: Relevance
“…An example of the latter is the study of terHorst et al (), in which the impact of evolution of a plant to drought stress was studied on community composition of soil bacteria. The table excludes studies that address interaction modules such as predator–prey interactions (e.g., Becks et al, ; Hiltunen & Becks, ; Yoshida et al, ), host–parasite interactions (Brunner et al, ; Decaestecker et al, ; Frickel et al, ; Masri et al, ) and host–mutualist interactions (Ford et al, ; Macke et al, ), unless they involved whole communities of predators, prey, hosts, parasites or mutualists. Most eco‐evolutionary studies of predator–prey and host–parasite interactions involve one species of each type of interactors (predator and prey, host and parasite), and thus, while taking a two‐species approach, they do not allow estimating the degree to which evolution of competing predators or prey influence dynamics.…”
Section: Key Studies On Eco‐evolutionary Dynamics In a Community Contextmentioning
confidence: 99%
“…An example of the latter is the study of terHorst et al (), in which the impact of evolution of a plant to drought stress was studied on community composition of soil bacteria. The table excludes studies that address interaction modules such as predator–prey interactions (e.g., Becks et al, ; Hiltunen & Becks, ; Yoshida et al, ), host–parasite interactions (Brunner et al, ; Decaestecker et al, ; Frickel et al, ; Masri et al, ) and host–mutualist interactions (Ford et al, ; Macke et al, ), unless they involved whole communities of predators, prey, hosts, parasites or mutualists. Most eco‐evolutionary studies of predator–prey and host–parasite interactions involve one species of each type of interactors (predator and prey, host and parasite), and thus, while taking a two‐species approach, they do not allow estimating the degree to which evolution of competing predators or prey influence dynamics.…”
Section: Key Studies On Eco‐evolutionary Dynamics In a Community Contextmentioning
confidence: 99%
“…For example, Brunner et al. () demonstrated that the sole presence of a fish parasite in an experimental ecosystem alters the abiotic environment of the host in terms of nutrient content or dissolved oxygen. These altered environments were shown to impose selection on a subsequent generation of hosts, hence evidencing that macroparasites can mediate eco‐evolutionary feedbacks between fish and their environment.…”
Section: Eefs Involving Two Speciesmentioning
confidence: 99%
“…Such ecological feedbacks occur when interactions at one time determine the performance or interactions of organisms at another (Hendry, 2016). The impact of nutrient availability has already been demonstrated to alter eco-evolutionary dynamics in plants and in fish due to increased eutrophication, resulting in changes to parasite load and individual feeding ecology (Anaya-Rojas et al, 2016;Brunner et al, 2017). Future research will thus not only have to focus on direct effects of N and P on species but also on how they impact the interactions between species at the ecosystem level.…”
Section: Future Research Prioritiesmentioning
confidence: 99%